2018
DOI: 10.1016/j.clinbiomech.2017.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Upper torso pain and musculoskeletal structure and function in women with and without large breasts: A cross sectional study

Abstract: Differences in the upper torso posture, range-of-motion, and muscle strength of women with large breasts provides insight into underlying causes of their musculoskeletal pain. This information can be used to develop evidence-based assessment and treatment strategies to relieve and prevent symptom progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
1
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(41 citation statements)
references
References 33 publications
(62 reference statements)
2
36
1
2
Order By: Relevance
“…Outside the reduction mammoplasty literature, there is growing evidence of the potential impact of larger breast sizes on aspects of physical health including perceptions of pain and physical activity. Pain felt in the thoracic spine 26,27 and upper back and torso 28,29 has been observed more commonly in women with large breasts across a range of ages who are not seeking reduction mammoplasty. Total time spent in physical activity and participation in vigorous physical activity have also been noted to be significantly lower among women (aged 18-75 years) with hypertrophic breasts compared to women with small breasts.…”
Section: But Also Because With Advancingmentioning
confidence: 99%
“…Outside the reduction mammoplasty literature, there is growing evidence of the potential impact of larger breast sizes on aspects of physical health including perceptions of pain and physical activity. Pain felt in the thoracic spine 26,27 and upper back and torso 28,29 has been observed more commonly in women with large breasts across a range of ages who are not seeking reduction mammoplasty. Total time spent in physical activity and participation in vigorous physical activity have also been noted to be significantly lower among women (aged 18-75 years) with hypertrophic breasts compared to women with small breasts.…”
Section: But Also Because With Advancingmentioning
confidence: 99%
“…A change in body posture combined with non-ergonomic work affects the emergence of pain, as evidenced by Nowotny et al [14]. The results of these studies also seem to be confirmed in three studies proving that the size of the breasts is associated with pain of the musculoskeletal system [9][10][11]. Chao et al studied the usefulness of removing breast tissue in symptomatic patients (regardless of amount of tissue removed) to improve their physical disabilities related to breast hypertrophy, and in turn, improve their quality of life.…”
Section: Discussionmentioning
confidence: 75%
“…In the reviewed studies, three studies [9][10][11] proved that the size of the breasts is associated with pain of the musculoskeletal system. The above results were explained by Schinkel-Ivy et al according to whom the torso muscles showed positive, moderately strong correlations with the size of the breast while standing and some movements of the trunk [3].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whilst UBP could share a number of risk factors reported to be relevant to low back and neck pain, such as poor muscle function and non-neutral postures [12, 13], it is also likely that the condition has unique risk factors that relate more specifically to the anatomy and function of the upper torso and thoracic spine. A unique risk factor in women could be breast size, as this conceivably affects upper torso mechanics [14] and has been associated with UBP in postmenopausal women [15]. Breast size [16] and breast characteristics [17] commonly change following menopause, and whilst these characteristics have been reported to explain some of the variance in UBP in women aged 18–82 years (mean (SD) age 41 (19) years) [18], their importance and contribution to UBP alongside other potentially relevant physical characteristics, has not been previously explored.…”
Section: Introductionmentioning
confidence: 99%